Literature Review on Detecting Bubbles in Stock Market - Adrianna Syariefur Rakhmat; Mohammad Hatta Fahamsyah (East Asian Journal of Multidisciplinary Research, 2023)
Stock market bubbles are times when valuation dynamics are momentarily explosive. Stock bubbles can be interpreted as a deviation of stock prices from their fundamental value. LPPLS is one of model to calculate bubble, which assuming that an asset's observed price trend during a bubble era differs from its intrinsic fundamental value. This research is qualitative study or descriptive research to review the LPPLS as a model to calculate bubbles in stock. This study uses secondary data sourced from articles which published in Scopus Indexed International Journal. The conclusion of the research that the LPPLS model can calculate, predict and identify accurately bubbles related  historical event such as the black Monday, dot com, and subprime crisis periods. The LPPLS model has the advantage, including construct end of bubble signals accurately.